Katnis Everdeen's Ambition In The Hunger Games Trilogy Novel (2008 - 2010) By Suzanne Collins:A Psychoanalytic Approach - Rahayu, Titis Sri; , Titis Setyabudi, S.S. M. Hum (2017)
The main issue of this research is ambition.Everybody needs ambition to reach their aim.The purpose of this research paper is to analyze ambition reflected in The Hunger games trilogy novel especially on the main character of the novel, Katnis Everdeen based on Psychological approach. The researcher used qualitative method. The researcher used two data sources: Primer and Secondary. The Primer data was The Hunger games trilogy novel: The Hunger Games (2008), Catching Fire (2009), and Mocking jay (2010) by Suzanne Collins. The sources of secondary data are taken from other sources related the study, such as: Internet (website), dictionary, and some books which support the research. For data analysis, the researcher used descriptive qualitative research. Based on analysis, the researcher took some conclusions. This study reveals that ambition is something that everyone, no matter their age or culture background, instinctively. Ambition can be a driving force for success, or in some cases a road to failure. Through ambitious undertakings Katnis can set goals and find her selves and her God-given talents. Katnis Everdeen with her ambition can Hunger Games will be over, and then finds Freedom to life, speak, society, free from starvation and freedom without suppression from government. Keyword: Ambition, the Hunger Games trilogy, Suzanne Collins, Psychoanalytic